Control systems theory for linear repetitive processes - recent progress and open research problems - Rogers, Eric; Gałkowski, Krzysztof; Owens, David H. (Zielona Góra: Uniwersytet Zielonogórski)
The unique feature of a repetitive process is a series of sweeps, termed passes, through a set of dynamics defined over a finite duration known as the pass length. On each pass an output, termed the pass profile, is produced which acts as a forcing function on, and hence contributes to, the next pass profile. This, in turn, is the source of the unique control problem for these processes in that the output sequence of pass profiles can contain oscillations that increase in amplitude in the pass to pass direction.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka